Governance by indicators global power through quantification and rankings - Davis, Kevin E.; New York University. Institute for International Law and Justice (Oxford : Oxford University Press, 2012)
Indicators and rankings are widely used by governments and organisations to assess the effectiveness, efficiency, and success of policy decisions. This book evaluates the creation of indicators, their impact on policy decisions, and the implications of their use.
At foot of title: Institute for International Law and Justice New York University School of Law.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Political indicators; Ranking and selection (Statistics)